Design of shunt hybrid active power filter for compensating harmonic currents and reactive power - Ibrahim Alhamrouni; F. N. Hanafi; Mohamed Salem; Nadia H. A. Rahman; Awang Jusoh; Tole Sutikno (Universitas Ahmad Dahlan, 2020)
For the past two decades, tremendous advancements have been achieved in the electricity industry. The usage of non-linear loads in the daily life has affected the power quality of the system and caused the presence of harmonics. To compensate the harmonic currents and reactive power in the system, the design of shunt hybrid active power filter has been proposed in this research. The design of the filter has included several control systems of instantaneous active and reactive power (p-q) theory and PI controller to investigate the performance of the filter. The robustness of the designed hybrid power filter has also been benchmarked with the other filter topologies available in literature. The hybrid power filter will combine passive power filter and active power filter configurated in shunt connection. The result of this research showed that the total harmonic distortion analyzed is below than 5% according to IEEE-519 standard requirements and reactive power is compensated proved by the increase in power factor. The shunt hybrid active power filter is designed, and simulation result is analyzed by using MATLAB-Simulink environment.